PENGGUNAAN FAKTOR PRODUKSI USAHATANI CAISIM (Brassica chinensis L.) - Muzalifah, Muzalifah; Danapriatna, Nana; Nursinah, Is Zunaini (Fakultas Pertanian Universitas Islam 45 (UNISMA) Bekasi, 2010)
This study aims to determine the factors that affect the amount of production in one growing season and measure the efficiency of production factors for a one-time harvest. The method used in this study is a survey method with the case in Kampung Rawa Ants RT / RW 04/12 Margahayu Village, East Bekasi. A total of 30 farmers caisim as respondents. The analysis model used is the Cobb-Douglas models, followed by analysis of the elasticity of production factors. The results showed that (a) chicken manure significantly affect yield while seed, urea fertilizer , KCl fertilizer, NPK fertilizer, TSP fertilizers and pesticides have no effect, (b) the use of factors of production is not efficient KCl fertilizer, chicken manure fertilizer and pesticides, while seeds, urea fertilizers , NPK and TSP fertilizer inefficient.